Kajian Stilistika pada Novel Laskar Pelangi Karya Andrea Hirata - Ambo Intang; Ramly Ramly (JENTERA: Jurnal Kajian Sastra, 2025)
This study aims to describe the uniqueness of vocabulary selection, the distinctiveness of morphological and syntactic structures, and the use of figurative language in Andrea Hirata's novel Laskar Pelangi. A descriptive qualitative approach was used in this study. Data was collected using observation and note-taking techniques. The novel was analyzed as a single text to identify distinctive vocabulary, morphological and syntactic structures, and figurative language styles that characterize Andrea Hirata's writing style. Data analysis used the flow model of analysis, which includes three stages: data reduction, data presentation, and conclusion drawing. The results of the study indicate that the stylistics of the novel Laskar Pelangi are not only evident in the inspiring plot but also in the lexical richness that reflects the author's social, cultural, and educational background. Morphologically, the use of affixation, reduplication, and compounding enriches word structure, while syntactically, discourse and sentence structure are arranged dynamically and communicatively. Figurative language styles such as metaphors, personification, similes, idioms, and hyperbole provide aesthetic and emotional nuances, strengthening the reader's connection to the text. The novel Laskar Pelangi demonstrates a distinctive stylistic approach and contributes to the aesthetic appeal of modern Indonesian literature. Abstrak Penelitian ini bertujuan untuk mendeskripsikan keunikan pemilihan kosakata, kekhasan struktur morfologis dan sintaktis, serta penggunaan gaya bahasa figuratif dalam novel Laskar Pelangi karya Andrea Hirata. Pendekatan kualitatif deskriptif digunakan pada penelitian ini. Data dikumpulkan menggunakan teknik simak dan catat. Novel dianalisis sebagai teks tunggal untuk mengidentifikasi kosakata khas, struktur morfologis dan sintaksis, serta gaya bahasa figuratif yang membentuk ciri kepengarangan Andrea Hirata. Analisis data menggunakan model analisis flow model of analysis mencakup tiga tahap reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa stilistika novel Laskar Pelangi tidak hanya tampak dalam alur cerita yang inspiratif, tetapi juga dalam kekayaan leksikal yang mencerminkan latar sosial, budaya, dan pendidikan penulis. Secara morfologis, penggunaan afiksasi, reduplikasi, dan pemajemukan memperkaya struktur kata, sementara secara sintaksis, susunan wacana dan kalimat disusun secara dinamis dan komunikatif. Gaya bahasa figuratif seperti metafora, personifikasi, simile, idiom, dan hiperbola memberikan nuansa estetis dan emosional, memperkuat keterikatan pembaca terhadap teks. Novel Laskar Pelangi menunjukkan stilistika yang khas dan berkontribusi pada daya tarik estetik karya sastra modern Indonesia.